Analisis Pemeliharaan Sarana Dan Prasarana Kantor Pada PT. Radiant Utama Interinsco - Faadiyah Aulia Rihhadatul ‘Aisy; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
The achievement of a company's goals can be determined from the maximum planning that has been carried out. This effort can be made by identifying the resources owned, such as office facilities and infrastructure. This research aims to determine the implementation and obstacles to maintaining office facilities and infrastructure at PT. Radiant Utama Interinsco. This research method uses qualitative descriptive research. The population and sample in this study were employees of PT. Radiant Utama Interinsco. The data collection techniques used were observation, interviews and documentation. The data that has been obtained is then analyzed descriptively using triangulation techniques. The research results show that maintenance of office facilities and infrastructure at PT. Radiant Utama Interinsco has been optimized. Maintenance carried out is in the form of routine, preventive and repressive maintenance. The maintenance schedule is determined once a year centrally. There are six times for maintaining office facilities and infrastructure, namely daily, weekly, monthly, quarterly, six months and annually. Barriers to maintaining office facilities and infrastructure are the age of the existing office facilities and infrastructure and the lack of employee awareness of the use of office facilities and infrastructure.